The Role Of Human Resource Management In Improving Teacher Performance In The Independent Learning Curriculum: (Case Study Of Public Primary Schools In Cibeber District - Cilegon City) - Fathiyatuddini Fathiyatuddini; Hamdan Hamdan (International Journal of Economics, Management and Accounting, 2024)
The focus of this research is the role of human resource management in improving teacher performance in Cibeber District, Cilegon City in terms of implementing management functions in the Independent Learning Curriculum. This research uses a qualitative approach, data collection techniques through observation, interviews and documentation, data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of the research show that the role of Human Resource Management in improving teacher performance in Cibeber District , Cilegon City, namely by planning, organizing, directing and supervising, can be said to be quite good. First, planning by conducting a needs analysis and providing understanding regarding the The Independent Learning Curriculum and learning tools that must be prepared by teachers. Second, organizing by placing and dividing tasks according to abilities and educational background. Third, direction is carried out by providing direction and guidance regarding the tasks and responsibilities given as well as providing motivation in the form of giving awards for teacher performance achievements. Fourth, supervision is carried out by the school principal through class visits and supervisors from the Education Management Unit. The implications of the research results suggest that elementary schools provide training to teacher councils regarding learning media so that the communication and educational interaction process between teachers and students can take place appropriately, try to increase the availability of facilities and infrastructure for the smoothness and success of the learning process, and work together to improve each other. teacher performance, both from school principals, education staff, teaching staff (teachers), and school supervisors within the Education Management Unit and it is hoped that everything that has been achieved can be improved.